TANGGUNG JAWAB ORANG TUA KEPADA ANAK DALAM Q.S. LUQMAN AYAT 12-19 : (Telaah Penafsiran Al-Mawardi Dan Al-Maraghi) - Gunawan, Nofri; Musli, Musli; Arifullah, Mohd; Setiawan, Heru (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2022)
Moral education is the main foundation in Islamic teachings and the foundation of belief to be used as a basis for all attitudes and behavior given through parents. Children are a source of happiness and conditioning and the most significant trust Allah SWT gives to every parent in the world. Therefore, children are the responsibility of parents. However, including parents, humans are not immune from mistakes, mistakes, and forgetfulness. Many parents need to remember the responsibility of fulfilling their children's rights. This research is library research that uses various sources of literature as a source of research data. Primary data sources are al-Mawardi's commentary, Al-Nukat Wa Al-'Uyun's interpretation, and Mustafa al-Maraghi's interpretation of al-Maraghi. In contrast, secondary data sources in research are books, articles, magazines, newspapers, or other sources. The results of this study are Al-Maraghi and Al-Mawardi. Both of them were reluctant that a child should be taught to worship Allah alone and not associate anything with Him. Then the responsibility of parents in educating children, according to surah Luqman, is by instilling the concept of believing in Allah by not giving Him glory, believing in the Prophets and Messengers, believing in the Books, obeying Allah by praying and doing good to parents, amar ma'ruf nahi mungkar. Luqman forbade his son not to associate partners with Allah with anything because there is no greater injustice than associating partners with Allah with others. Pendidikan akhlak merupakan fondasi utama dalam ajaran Islam dan dasar-dasar pokok kepercayaan untuk dijadikan pijakan dalam segala sikap dan tingkah lakunya yang diberikan melalui orang tua.Anak sebagai sumber kebahagian dan penyejuk hati, dan amanah terbesar yang Allah swt berikan kepada setiap orang tua di dunia. Karenanya, anak adalah tanggung jawab orang tua. Namun, Manusia tidak luput akan kesalahan, kesilapan dan kelupaan termasuk orang tua. Banyaknya, orang tua yang lupa dengan tanggung jawab dalam menunaikan hak-hak anaknya. Penelitian ini merupakan penelitian kepustakaan (Library research) yang menggunakan berbagai sumber kepustakaan sebagai sumber data penelitian. Sumber data primer adalah buku tafsir al-Mawardi yaitu tafsir Al-Nukat Wa Al-‘Uyun dan tafsir al-Maraghi karangan Mustafa al-Maraghi, Sedangkan Sumber data sekunder dalam penelitian adalah buku, artikel, majalah, surat kabar, atau sumber lainnya. Hasil penelitian ini adalahAl-Maraghi dan Al-Mawardi. Keduanya telah sepakat, bahwa hendaklah seorang anak diajarkan untuk menyembah Allah saja dan tidak menyekutukan-Nya dengan sesuatu apapun. Kemudian tanggung jawab orang tua dalam mendidik anak menurut surah Luqman yaitu dengan cara menanamkan konsep beriman kepada Allah dengan tidak menyukutakn-Nya, beriman kepada Nabi dan Rasul, beriman kepada Kitab-kitab, Ta’at kepada Allah dengan Shalat dan berbuat baik kepada orang tua, amar ma’ruf nahi mungkar, serta Luqman melarang putranya agar tidak menyekutukan Allah dengan sesuatu apapun, karena tidak ada kazhaliman yang lebih besar daripada menyekutukan Allah dengan lainnya.